EU MARGINAL:(DES)ENCONTROS NARRATIVOS EM PRIMEIRA PESSOA - Navarro, Luciane Pereira da Silva (2014)
Focused on the investigation of the marginal identity language in the traditional editorial and on the blogosphere, this case study articulates a comparative analysis between two narrations in the first person. The popular women’s magazine Sou mais Eu, published by Abril publisher, provides this study with a report on the story of life of Melita Luzia Santos. This text is compared to narration, with no journalistic mediation of the protagonist in her personal blog, Saída de Emergência (Emergency Exit). According to the discussion interlined in Phillipe Lejeune on the Pacto Autobiográfico (The Autobiographical Pact), both the magazine and the blog are autobiographic with different degrees of subordinate representation and writing opening. Both texts selected have a grammatical “I” that refers to the name of Melita Luzia dos Santos, the difference between them is in the fact that on the magazine the journalist is the one who writes it while on the blog the protagonist is the one who writes it. On this dichotomy, the usage or misusage of “I” in the narrations are compared from the conception of an identity language, these proposed by Roland Barthes on O Grau Zero da Escritura (Writing Degree Zero). This work has also provided the theoretical support to choose Quarto de Despejo (Beyond All Pity), by Carolina Maria de Jesus, as the referential model of truth functional language. The choice of this methodological approach has been crucial to accomplish the analysis out of the limits imposed by a spelling and andocentric culture that would, likely, point at a traditional linguistic analysis. Michel Foucault with the text A vida dos Homens Infames (The Life of Coward Men) and Gayatri Spivak with the work Pode o Subalterno Falar?(Can the Subaltern Speak?) compose the theoretical surrounding that, in the end, lies over subordinate female self-narrations in contemporaneity, whose extent and contextual implications required the usage of the dialectic method.